Numerical Investigation on Fluid Flow in a 90-Degree Curved Pipe with Large Curvature Ratio. (17th August 2015) - Wang, Yan; Dong, Quanlin; Wang, Pengfei
Abstract : In order to understand the mechanism of fluid flows in curved pipes, a large number of theoretical and experimental researches have been performed. As a critical parameter of curved pipe, the curvature ratioδ has received much attention, but most of the values ofδ are very small (δ < 0.1 ) or relatively small (δ ≤ 0.5 ). As a preliminary study and simulation this research studied the fluid flow in a 90-degree curved pipe of large curvature ratio. The Detached Eddy Simulation (DES) turbulence model was employed to investigate the fluid flows at the Reynolds number range from 5000 to 20000. After validation of the numerical strategy, the pressure and velocity distribution, pressure drop, fluid flow, and secondary flow along the curved pipe were illustrated. The results show that the fluid flow in a curved pipe with large curvature ratio seems to be unlike that in a curved pipe with small curvature ratio. Large curvature ratio makes the internal flow more complicated; thus, the flow patterns, the separation region, and the oscillatory flow are different.